Livestock grazing in forest by livestock dependent forest dwelling communities - SAMAJDAR, TANMAY; CHANDER, MAHESH (The Indian Journal of Animal Sciences, 2014)
The livestock keeping forest dwelling communities are viewed by the forestry experts, economists and other agencies as a cause of forest depletion while anthropologists and ecologists have argued that the pastoralists have developed sustainable mode of pasture management based on sound knowledge of forest ecosystem. The arguments in this regard Including the relocation of such communities are manifold and well documented. One such community called Van Gujjars who solely sustain on animal husbandry inside the forest of North India was studied to doclimenr their livestock rearing practices mainly. Van Gujjars rear the buffaloes totally on forest grazing and tree fodder lopping. They pay grazing fee to the forest department but it is vety nominal vis-a-vis the area grazed, livestock maintained. trees lopped and earning made by the Van Gujjars through sale of milk and milk-products. Moreover, the Van Gujjars had. no responsibility towards afforestation and maintenance of forests. The relationship of van Gujjars with the forests appeared to be purely extractive since no arrangement to secure the participation of this community in forest management was in vogue. Whereas. the relocation efforts for this community have so far not met with success. The mechanisms, therefore. need to be evolved wherein effective participation of Van Gujjars is ensured towards sustainability and better productivity af forests along with the socioeconomic and cultural wellbeing of this community since their existence outside forest appears to be a difficult aiternative at the moment.